2013
DOI: 10.2217/fmb.13.38
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Transformations of Arsenic: Perspectives for Biological Removal of Arsenic from Water

Abstract: Arsenic is present in many environments and is released by various natural processes and anthropogenic actions. Although arsenic is recognized to cause a wide range of adverse health effects in humans, diverse bacteria can metabolize it by detoxification and energy conservation reactions. This review highlights the current understanding of the ecology, biochemistry and genomics of these bacteria, and their potential application in the treatment of arsenic-polluted water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 123 publications
4
54
0
Order By: Relevance
“…Previously, many studies have revealed the widespread distribution of arsenic-related genes in bacteria, and arsenic-related genes have been isolated from a large number of bacteria from different niches [1], [4], [8], [9], [11], [13], [41]. In light of these data, it has been assumed that arsenic-related genes were common in all bacteria, but clear evidence has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, many studies have revealed the widespread distribution of arsenic-related genes in bacteria, and arsenic-related genes have been isolated from a large number of bacteria from different niches [1], [4], [8], [9], [11], [13], [41]. In light of these data, it has been assumed that arsenic-related genes were common in all bacteria, but clear evidence has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, aqueous arsenic contamination can be removed through biological oxidation of ferrous iron, as the precipitating ferric (oxyhydr)oxides bind arsenic (Katsoyiannis and Zouboulis 2004). Thus, the activity of iron-reducing and oxidizing microorganisms indirectly affects arsenic concentrations in groundwater, in addition to the activity of specific microorganisms directly involved in the biogeochemical cycling of arsenic: arsenate-reducing bacteria releasing arsenite [As(III)] and arsenite-oxidizing bacteria producing arsenate [As(V)], which is less toxic, less mobile, and binds better to ferric (oxyhydr)oxides than arsenite (Cavalca et al 2013). Knowledge on the microbial ecology of the iron cycle in relation to the generation and remediation of arsenic contaminated drinking water in South and Southeast Asia is still limited, in particular with respect to iron oxidation potential.…”
Section: Location Physicochemical Parametersmentioning
confidence: 99%
“…Numerous microorganisms can gain energy using As either as electron donor (chemolithotrophic As III -oxidizing bacteria, AOB) (Oremland et al 2002) or as electron acceptor (dissimilatory As V -reducing bacteria, DARB) (Ahmann et al 1994). The microorganisms able to utilize As have demonstrated a great phylogenetic diversity, and they can be found in aquatic and terrestrial environments, as well as in a wide range of environmental conditions (Cavalca et al 2013, Kruger et al 2013). …”
Section: Introductionmentioning
confidence: 99%